A Novel Route for Immobilization of Proteins to Silica Particles Incorporating Silaffin Domains - Nam, Dong Hyun; Won, Keehoon; Kim, Yong Hwan; Sang, Byung In (WILEY, 2009)
In the diatom Cylindrotheca fusiformis, modified peptides called silaffin polypeptides are responsible for silica deposition in vivo at ambient conditions. Recently, it was discovered that the synthetic R5 peptide, the repeat unit of silaffin polypeptide without post-translational modification, was capable of precipitating silica in vitro and at ambient conditions. Herein, chimeric proteins were generated by incorporating synthetic silaffin R5 peptides and related unmodified silaffin domains (R1-R7) from Cylindrotheca fusiformis onto green fluorescent protein (GFP) by recombinant DNA technology and their ability to cause silicification was also examined. GFP chimeric proteins showed silicification at very low concentrations (600-700 mu g/mL) when compared with adding excess amounts of R5 peptides (10 mg/mL) as previously reported. Sensitive to pH conditions, only the GFP-R1 chimera showed silicification activity at pH 8.0. The protein immobilization efficiencies of these chimeras were unexpectedly high ranging from 75 to 85%, with the RI silaffin-protein construct showing excellent immobilization efficiency and a constant molar ratio of silica to protein ranging from 250 to 350 over a wide pH range. The average silica particle sizes had a tendency to decrease as pH increased to basic conditions. This study demonstrated the production of nanoscale immobilized protein, fabricated via silaffin-fused proteins. (C) 2009 American Institute of Chemical Engineers Biotechnol. Prog., 25: 1643-1649, 2009
Keywords: DIATOM BIOSILICA; BIOCATALYSIS; PEPTIDES; ENZYMES